PENYULUHAN TENTANG BAHAYA CEMARAN LOGAM BERAT PADA MATA AIR PEGUNUNGAN DI DESA LEBANG MANAI UTARA, KEC. RUMBIA, KAB. JE’NEPONTO - Rustiah, Wa Ode; Imran Amin; Dewi Arisanti; Sitti Normawati; Herlinda Mahdania; Andi Fatmawati (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2025)
Mountain spring water is often considered a source of clean, natural water. However, the potential contamination by heavy metals, due to both geological factors and human activities, poses serious health risks. Health is a crucial component of human life and key to living a prosperous life. Reducing risk factors for diseases is one way to achieve optimal health. This community service activity aims to increase the knowledge of the people in Lebang Manai Utara Village, Rumbia Subdistrict, Jeneponto Regency, about the dangers of heavy metal contamination and preventive measures. The method used is visual and interactive-based counseling, accompanied by pre-test and post-test evaluations. The results of the activity show a significant improvement in the community's understanding of contamination sources, health impacts, and the importance of water quality testing. This program is expected to encourage proactive behavior in maintaining the quality of drinking water.